2014
DOI: 10.1016/j.tvjl.2013.10.025
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility and repeatability of cold and mechanical quantitative sensory testing in normal dogs

Abstract: Feasibility and inter-session repeatability of cold and mechanical quantitative sensory testing (QST) were assessed in 24 normal dogs. Cold thermal latencies were evaluated using a thermal probe (0 °C) applied to three pelvic limb sites. Mechanical thresholds were measured using an electronic von Frey anesthesiometer (EVF) and a blunt-probed pressure algometer (PA) applied to the dorsal aspect of the metatarsus. All QST trials were performed with dogs in lateral recumbency. Collection of cold QST data was easy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
58
1
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 52 publications
(63 citation statements)
references
References 20 publications
3
58
1
1
Order By: Relevance
“…The test‐retest validity method for this tool may not be useful because CMSM is a progressive disease with signs frequently changing and worsening. Ideally, it would be tested for criterion validity, but there currently is no gold standard objective method of evaluating neuropathic pain in dogs; however, techniques such as quantitative sensory thresholds and nociceptive withdrawal reflex may have utility . The use of the words “pain” and “scratching” in the ChiMPS‐T questions could introduce respondent bias; therefore, wording may need to be altered to increase validity of this tool.…”
Section: Discussionmentioning
confidence: 99%
“…The test‐retest validity method for this tool may not be useful because CMSM is a progressive disease with signs frequently changing and worsening. Ideally, it would be tested for criterion validity, but there currently is no gold standard objective method of evaluating neuropathic pain in dogs; however, techniques such as quantitative sensory thresholds and nociceptive withdrawal reflex may have utility . The use of the words “pain” and “scratching” in the ChiMPS‐T questions could introduce respondent bias; therefore, wording may need to be altered to increase validity of this tool.…”
Section: Discussionmentioning
confidence: 99%
“…These objective assessments are less expensive and less complicated to use than force plates and offer easy longitudinal assessment for OA interventions and disease progression [174][175][176][177] . Many other tests could be useful in OA monitoring, including thermal imaging and mechanical nociceptive threshold testing 178,179 . Functional activity monitoring, force plate analysis and advanced MRI are performed on dogs in a manner that mirrors their use in human patients, and brain imaging in conscious pet dogs is also reliable and practical and could potentially be used for comparative neuroscience studies 180,181 .…”
Section: A Means To Identify the Genetic Basis Of Analogous Diseasementioning
confidence: 99%
“…Commonly, von Frey filaments have been used in humans with SM15, 16 and in various studies of pain in dogs 23, 25, 26, 27, 28, 29, 32, 33. The use of von Frey mechanical testing has been found to be feasible and reliable31, 33 and in 1 study identified different thresholds in normal dogs compared to dogs with acute spinal cord injury 32. However, a lack of association between normal dogs and dogs with chronic pain also has been noted using von Frey techniques 23.…”
Section: Discussionmentioning
confidence: 99%